KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI SUPERVISI AKADEMIK DI SD NEGERI 004 SUNGAI MANAU - Asnidawati Asnidawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the still many weaknesses found in teachers, especially in the preparation of learning implementation plans. The purpose of this study is to improve teacher competency in preparing plans for implementing learning through academic supervision. This research was conducted at 004 Sungai Manau Elementary School with 9 teachers. This study uses a school action research consisting of two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The results of the research prove, in the first cycle, the average value of the overall teacher in preparing the implementation of learning plans amounted to 67.5 with enough assessment categories. After conducting the assessment in the second cycle, the results of the assessment of the preparation of the learning implementation plan increased to 88.4 with a very good category. It can be concluded that through academic supervision in 004 Sungai Manau State Elementary School can increase teacher competence in developing learning implementation plans